Peran Remaja Muslim dalam Mempersiapkan Kepemimpinan Islam di Era Kontemporer - M. Khair; Ahmad Aspiani (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
In a contemporary era characterized by rapid social, technological, and cultural changes, the role of Muslim adolescents in preparing for Islamic leadership is crucial. Teenagers are the next generation who have great potential to bring Islamic values into the lives of modern society. This article aims to analyze how Islamic character education, the integration of Islamic values with modern leadership competencies, and the involvement of teenagers as agents of social change can shape adaptive and integrity Islamic leadership. This research uses a descriptive qualitative approach through a literature study of various scientific literature and supporting documents. The results show that Islamic values-based youth leadership development, accompanied by character strengthening and positive utilization of digital media, is an effective strategy in producing future Muslim leaders who are able to answer global challenges without losing their spiritual identity.